Disease-Induced Skeletal Muscle Atrophy and Fatigue - Powers, Scott K. (Med Sci Sports Exerc, 2016)
Numerous health problems including acute critical illness, cancer, diseases associated with chronic inflammation, and neurological disorders often result in skeletal muscle weakness and fatigue. Disease-related muscle atrophy and fatigue is an important clinical problem because acquired skeletal muscle weakness can increase the duration of hospitalization, result in exercise limitation, and contribute to a poor quality of life. Importantly, skeletal muscle atrophy is also associated with increased morbidity and mortality of patients. Therefore, improving our understanding of the mechanism(s) responsible for skeletal muscle weakness and fatigue in patients is a required first step to develop clinical protocols to prevent these skeletal muscle problems. This review will highlight the consequences and potential mechanisms responsible for skeletal muscle atrophy and fatigue in patients suffering from acute critical illness, cancer, chronic inflammatory diseases, and neurological disorders.